Molecular analysis of the bacterial microbiota in the human stomach - Bik, Elisabeth M. (National Academy of Sciences, 2006)
The microbiota of the human stomach and the influence of Helicobacter pylori colonization on its composition remain largely unknown. We characterized bacterial diversity within the human gastric mucosa by using a small subunit 16S rDNA clone library approach and analyzed 1,833 sequences generated by broad-range bacterial PCR from 23 gastric endoscopic biopsy samples. A diverse community of 128 phylotypes was identified, featuring diversity at this site greater than previously described. The majority of sequences were assigned to the Proteobacteria, Firmicutes, Actinobacteria, Bacteroidetes, and Fusobacteria phyla. Ten percent of the phylotypes were previously uncharacterized, including a Deinococcus-related organism, relatives of which have been found in extreme environments but not reported before in humans. The gastric clone libraries from 19 subjects contained H. pylori rDNA; however, only 12 of these subjects tested positive for H. pylori by conventional laboratory methods. Statistical analysis revealed a large degree of intersubject variability of the gastric ecosystem. The presence of H. pylori did not affect the composition of the gastric community. This gastric bacterial rDNA data set was significantly different from sequence collections of the human mouth and esophagus described in other studies, indicating that the human stomach may be home to a distinct microbial eco-system. The gastric microbiota may play important, as-yet-undiscovered roles in human health and disease.